2022
DOI: 10.3174/ajnr.a7657
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Collateral Scores Derived from Whole-Brain Time-Resolved Flat Panel Detector Imaging in Acute Ischemic Stroke

Abstract: BACKGROUND AND PURPOSE: Flat panel detector CT imaging allows simultaneous acquisition of multiphase flat panel CTA and flat panel CTP imaging directly in the angio suite. We compared collateral assessment derived from multiphase flat panel CTA and flat panel CTP with collateral assessment derived from DSA as the gold-standard. MATERIALS AND METHODS:We performed a retrospective analysis of patients with occlusion of the first or second segment of the MCA who underwent pre-interventional flat panel detector CT.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…HIR correlation with ASITN CS is well established, with studies showing a statistically significant correlation. The degree of correlation has been reported over a range of modest association (coefficient (r) = −0.33) [48] to moderate association (coefficient (r = −0.76) [19,49]. Our correlation was similar to Guenego et al [48], whereas it was lower than what was reported by Kurmann et al [19] and Ai et al [49].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…HIR correlation with ASITN CS is well established, with studies showing a statistically significant correlation. The degree of correlation has been reported over a range of modest association (coefficient (r) = −0.33) [48] to moderate association (coefficient (r = −0.76) [19,49]. Our correlation was similar to Guenego et al [48], whereas it was lower than what was reported by Kurmann et al [19] and Ai et al [49].…”
Section: Discussionsupporting
confidence: 78%
“…The degree of correlation has been reported over a range of modest association (coefficient (r) = −0.33) [48] to moderate association (coefficient (r = −0.76) [19,49]. Our correlation was similar to Guenego et al [48], whereas it was lower than what was reported by Kurmann et al [19] and Ai et al [49]. The wide range of variation in the correlation coefficient is multifactorial.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Substantial evidence is already available that modern flat-panel detectors can provide clinically reliable measures for collateral status both for flat-panel CTA and for flat-panel CTP. [24] , [25] Moreover, flat-panel imaging is constantly evolving, and diagnostic accuracies for haemorrhage and/or ischemic lesions are comparable to multidetector CT. However, limitations remain in the case of motion artifacts and in discerning between gray-white matter differentiation.…”
Section: Dtasmentioning
confidence: 99%